(untitled) (Grande Medical Journal, 2024)
Background Bone marrow aspiration is a safe procedure with a high degree of accuracy in the diagnosis of hematological disorders. This study was done to analyze the causes, spectrum of hematological disorders and interpret the bone marrow findings. Method This was a retrospective study of bone marrow aspiration (BMA) and biopsies done on 94 patients who were referred for bone marrow examination to the Department of Pathology of Grande International Hospital in the last 5 years. Cases were analyzed in detail regarding the clinical examination and other investigations. Result BMA from 94 patients were analyzed. 63 cases were male. The age of the patient ranged from 8 months to 85 years. The highest number of cases (44 cases, 46.08%) were in the age group of >45 years. PUO (42 cases, 44.68%) followed by pancytopenia (13 cases,13.82%) was the most common indication for BMA. Megaloblastic anemia (3 cases, 23.07%) and aplastic anemia (3 cases, 23.07%) was the most common cause of pancytopenia. Erythroid hyperplasia (23 cases, 24.46%) was the most common finding in BMA. Multiple myeloma (6 cases, 6.38%) followed by Acute Leukemia (5 cases, 5.31%) was the most common malignancy with AML (3 cases, 60%) more than ALL (2 cases, 40%). Conclusion Although bone marrow examination is an invasive procedure this is well tolerated by patients. The examination helps in many cases to arrive at a final diagnosis within a short period.